A Project Report on Multi Sensor Strategies to Asist Electer People with Bus Detection - ASHWINI L, HARSHITHA R, MADHUMATHI R and P KAVYA SREE P (2014)
INTERNAL GUIDE: MRS M BRINDHA, MVJCE
Keywords: Asist Electer People with Bus Detection